PERSPECTIVE OF MICROBIAL SPECIES USED IN LIGNOCELLULOSES BIOCONVERSION - S. PATHAK; H. S. CHAUDHARY (International Journal of Pharma and Bio Sciences, 2013)
Lignocellulosic wastes are abundant, renewable and inexpensive sources of energy. This wastes contains large amount of residual plant biomass which is non edible material obtained from plant cell walls. Biomass could be obtained from crop, domestic liquid fuel, municipal solid waste and agricultural residuals. In nature, cellulose, hemicellulose and lignin are major component of plant biomass therefore, their recycling is essential for the carbon cycle completion. In many countries environmental problems arises due to improper utilization of valuable waste materials. Lignocelluloses degradation is a difficult process due to presence of lignin which is an important constituent of plant cell wall. Lignocelluloses waste is degraded by a variety of microorganisms which produce a battery of enzymes that work synergically. Lignin degrading microorganisms required enzymes to convert lignocellulosic biomass into valuable carbohydrate source for the production of bio-ethanol, biogas and many more industrial products. Bioconversion of lignocellulosic residues is initiated by microorganisms such as fungi and bacteria which are capable of degrading lignocellulolytic materials. Among lignin degrading microbial species, white rot fungus are main due to the adequate presence of lignin degrading enzymes. This group of fungus (Basidiomycetes) are known to be efficient lignocelluloses degraders and considered to be the primary degraders of lignin and lignocellulosic materials in terrestrial ecosystems. In addition to that it is also necessary to develop the strains for conversion of lignocellulosic biomass to useful product. This review focuses on the variety of microorganisms known to degrade lignocellulosics their characteristics and involved mechanics/action and future prospects in lignocellulose bioconversion.